2007
DOI: 10.1590/s1678-77572007000600010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a post-polymerization treatments on the flexural strength and Vickers hardness of reline and acrylic denture base resins

Abstract: This study evaluated the effect of water-bath and microwave post-polymerization treatments on the flexural strength and Vickers hardness of four autopolymerizing reline resins (Duraliner II-D, Kooliner-K, Tokuso Rebase Fast-TR and Ufi Gel Hard C-UGH) and one heat-polymerized acrylic resin (Lucitone 550-L), processed using two polymerization cycles (short cycle - 90 minutes at 73°C and 100°C for 30 minutes; and long cycle - 9 hours at 71°C). For each material, thirty specimens (64 x 10 x 3.3 mm) were made and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 26 publications
1
21
0
1
Order By: Relevance
“…6,34 The flexibility of the polymer chain may account for the relatively lower VH. 35 the surface hardness. This is due to fact that, a large particle size gives rise to greater stress concentrations and contributes to the formation of larger cavities and voids between these particles with the presence NBR micro-size particles in PMMA composite.…”
Section: Discussionmentioning
confidence: 99%
“…6,34 The flexibility of the polymer chain may account for the relatively lower VH. 35 the surface hardness. This is due to fact that, a large particle size gives rise to greater stress concentrations and contributes to the formation of larger cavities and voids between these particles with the presence NBR micro-size particles in PMMA composite.…”
Section: Discussionmentioning
confidence: 99%
“…Seo et al 23) noted that no significant difference was found between the heat-polymerized acrylic resin specimens polymerized with short or long cycles for microhardness (p>0.05). In contrast, in the present study, the microhardness for specimens polymerized with the F cycle were significantly higher than those polymerized with the A cycle (p<0.05).…”
Section: Discussionmentioning
confidence: 98%
“…Seo et al 23) reported that flexural strengths of heatpolymerized acrylic resin, when polymerized for 90 min at 73°C and then 100°C boiling water for 30 min (short cycle), were higher than when it was polymerized for 9 h at 71ºC (long cycle). This finding is in accordance with the present study in which the specimens polymerized with the F cycle (90 min at 74°C and then 100°C boiling water for 30 min) had higher flexural strengths than with the A cycle (9 h at 74°C).…”
Section: Discussionmentioning
confidence: 99%
“…Heat-polymerized acrylics (HP) release less residual monomers than the SP ones once high temperatures promote higher degree of conversion and reduced powder (PMMA)/liquid (MMA) ratio in the mixture, affecting flexural strength [ 29 ]. Besides that, fiber reinforced resin can present voids and cracks (Figures 1(a) and 3(b) ).…”
Section: Discussionmentioning
confidence: 99%
“…Acrylic restorations reinforced with nonimpregnated fibers show lower fracture resistance than those reinforced with impregnated fibers [ 27 ]. However, the residual monomer release in autopolymerized or heat-polymerized acrylic resins [ 28 , 29 ] increases with the addition of preimpregnated fibers [ 27 ] and this could affect the strength of the reinforced material.…”
Section: Introductionmentioning
confidence: 99%